Meta-analysis of CYP2E1 polymorphisms in liver carcinogenesis. Issue 1 (January 2017) - Fu, Peiyao; Yang, Fan; Li, Bo; Zhang, Biao; Guan, Lianyue; Sheng, Jiyao; Ye, Yanshuo; Wang, Zhanpeng; Li, Peidong; Xu, Li; Zou, Liangjian; Li, Wei
Abstract: Background: The CYP2E1 protein is a monooxygenase with certain polymorphisms linked to liver cancer. However, results from individual studies remain controversial. Aims: To evaluate CYP2E1 polymorphisms in liver carcinogenesis through meta-analysis. Methods: All studies about CYP2E1 polymorphisms and liver cancer were retrieved from seven major databases. Original data from each study were pooled and re-analyzed. Results: Total of 16 articles with 4862 cases were selected, including 1820 cases of liver cancer and 3042 cases of controls. The c1 allelic frequency in the cases and controls was 83.3% and 85.3%, respectively. Five genetic variations were compared: dominant c1c2/c2c2 vs. c1/c1 (OR = 0.987 (0.853, 1.141)), homozygous c2c2 vs. c1c1 (OR = 0.767 (0.526, 1.119)), heterozygous c1c2 vs. c1c1 (OR = 1.005 (0.854, 1.182)), recessive c2c2 vs. c1c2/c2c2 (OR = 0.771 (0.530, 1.122)), and different alleles c2 vs. c1 (OR = 0.947 (0.828, 1.082)). Pooled data were further analyzed based on ethnicity, control sources, and HWE (Hardy–Weinberg equilibrium). These results from stratified groups were similar to that of nonstratified groups. Conclusions: Our meta-analysis results suggest that there is no evidence for a major role of CYP2E1 polymorphism in liver carcinogenesis, but do not rule out the possibility in certain cases.